Net meta-analysis of the therapeutic effect of Chinese Traditional fitness Qigong on patients with cervical spondylosis (中国传统健身气功对颈椎病患者治疗效果的网状Meta分析) - WANG Zhifeng (王智凤); CHEN Mengshi (陈梦诗); XIONG Qianfen (熊钱芬); WU Hongyan (吴宏燕) (Journal of International Translational Medicine Limited, 2024)
Objective A Bayesian net Meta-analysis was conducted to compare the efficacy of four traditional Chinese fitness Qigong techniques, namely, Baduanjin, Wuqinxi, Taijiquan, and Yijinjing, in treating cervical spondylosis, and their effects on pain relief and cervical spine function, in order to provide a reference for patients with cervical spondylosis in China in selecting the traditional fitness qigong treatment program. Methods Randomized controlled clinical trials on the treatment of cervical spondylosis with Ba Duan Jin, Taijiquan, Wu An Qigong and Yi Jin Jing were searched sequentially from PuBMed, Embase, Medline, CNKI, WanFang Data, VIP, and CBM, and the search time was set from the establishment of the database to August 7, 2023, and the results were reported by two researchers. Literature search and screening were performed by 2 researchers respectively, and then the included literature was subjected to data extraction and quality evaluation, using NoteExpress for literature screening, RevMan5. 4 software to draw literature risk of bias maps, the R software gemtc package, and JAGS software for Bayesian mesh meta-analysis, and stata17. 0 to draw the A "comparison-correction" funnel plot was drawn using stata17. 0 to evaluate whether there was publication bias in the included literature. Results A total of 40 papers were included, totaling 3236 patients with cervical spondylosis. Net Meta-analysis showed that in terms of total effectiveness, the top 3 fitness qigong programs were Baduanjin, Yijinjing, and Baduanjin + conventional treatment; In terms of VAS scores, the top 3 fitness qigong programs for pain reduction were Baduanjin, Yijinjing, and Taijiquan + conventional treatment; In terms of cervical vertebral dysfunction indices, the fitness qigong programs for cervical vertebrae improvement were Baduanjin + conventional treatment and Yijinjing. Conclusion Each of the four traditional Chinese fitness qigong exercises has its own advantages in the treatment of cervical spondylosis, and all of them have good clinical effects. However, this study showed that Ba Duan Jin is the best way to improve the efficacy and pain of patients with cervical spondylosis and has a good effect on cervical spondylosis patients of all ages. However, more high-quality randomized controlled trials are needed to confirm the results of this study, and doctors need to choose the best qigong according to the specific conditions of the patients in clinical treatment. (目的 采取贝叶斯网状Meta分析的方法比较八段锦、五禽戏、太极拳、易筋经4种中国传统健身气功治疗颈椎病的疗效以及对疼痛的缓解和颈椎功能的改善作用, 为国内颈椎病患者选取传统健身气功治疗方案提供参考依据。方法 依次检索数据PuBMed、Embase、Medline、中国知网(CNKI)、万方(WanFang Data)、维普数据库(VIP)、中国生物医学文献数据库(CBM)中有关八段锦、太极拳、五禽戏、易筋经治疗颈椎病的随机对照试验, 检索时限均为建库至2023年8月7日。由两名研究人员进行文献检索及筛选, 再将纳入的文献进行数据提取和质量评价, 使用NoteExpress软件进行文献筛选, RevMan5. 4软件绘制文献偏倚风险图, R软件gemtc包、JAGS软件进行贝叶斯网状meta分析, 使用Stata 17. 0绘制"比较-校正"漏斗图评价纳入文献是否存在发表偏倚。结果 共纳入40篇文献, 共计3236例颈椎病患者。网状Meta分析结果显示, 在总有效率方面, 疗效前3名的健身气功方案为八段锦、易筋经、八段锦+常规治疗; 在VAS评分方面, 减轻疼痛前3名的健身气功方案为八段锦、易筋经、太极拳＋常规治疗; 在颈椎功能障碍指数方面, 使颈椎功能得到改善的健身气功为八段锦+常规治疗、易筋经。结论 4种中国传统健身气功在治疗颈椎病时各有其优点, 皆具有良好的临床治疗效果。本研究显示八段锦是提高颈椎病患者疗效, 改善疼痛的最佳方式, 且对各年龄阶段的颈椎病患者都具有良好的改善作用, 但仍需要更多高质量的随机对照试验来证实其结果, 临床治疗时医生需根据患者的具体情况进行选择。)